2021
DOI: 10.1097/jan.0000000000000388
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent Girls and Alcohol Use: Increasing Concern During the COVID-19 Pandemic

Abstract: Adolescence is a time known for risky behaviors and often the initiation of alcohol use. Readily available, alcohol is often one of the drugs of choice for adolescents. Whereas in the past 30 years, the overall consumption of alcohol is down, the data in the past 10 years have shown more girls are binge drinking and meeting criteria for alcohol use disorder (AUD). The alarm of early alcohol use is the association with problems with the substances later in life. Historically, men and male adolescents consumed m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 22 publications
1
13
0
Order By: Relevance
“…The apparent sudden decrease when social restrictions were implemented and then the sharp escalation as restrictions were removed can partly be attributed to the evidence that male alcohol consumption and binge drinking may be more socially driven than that of females. For example, Smith and collegues [ 27 ] indicated that males tend to consume alcohol to have fun (i.e., enhance one's ability to experience positive emotions), whereas females drink to diminish their experience of negative emotions and relieve stress or depression [ 26 ]. Recently, the study by Romano et al., [ 28 ] found that some female Canadian high school students used alcohol to cope during the early months of the pandemic, particularly those with poorer psychosocial well-being.…”
Section: Discussionmentioning
confidence: 99%
“…The apparent sudden decrease when social restrictions were implemented and then the sharp escalation as restrictions were removed can partly be attributed to the evidence that male alcohol consumption and binge drinking may be more socially driven than that of females. For example, Smith and collegues [ 27 ] indicated that males tend to consume alcohol to have fun (i.e., enhance one's ability to experience positive emotions), whereas females drink to diminish their experience of negative emotions and relieve stress or depression [ 26 ]. Recently, the study by Romano et al., [ 28 ] found that some female Canadian high school students used alcohol to cope during the early months of the pandemic, particularly those with poorer psychosocial well-being.…”
Section: Discussionmentioning
confidence: 99%
“…In the current era of pandemic, in which heavy alcohol consumption has increased so much among young adults (Smith et al, 2021) and US excessive drinking projections by 2023 have estimated a dramatic increase of additional deaths (Julien et al, 2022), tools like the APNE can be useful for understanding positive and negative beliefs with regard to consumption and can therefore support policymakers to make informed decisions about the implementation of…”
Section: Discussionmentioning
confidence: 99%
“…Beyond pre-pandemic risk factors for depression, such as internalizing problems [ 14 , 15 , 16 ], some behaviors during the pandemic have contributed to greater risk for depression. For example, substance use has increased in some young adults, especially in women [ 17 ], contributing to mental health issues [ 18 ]. Poor sleep quality [ 19 ] and disrupted sleep, longer sleep latency, and higher daytime dysfunction [ 20 ] were prevalent among young adults during the COVID-19 outbreak, contributing to higher levels of depression than those reported in older adults.…”
Section: Introductionmentioning
confidence: 99%